A stealth antigen SPESP1, which is epigenetically silenced in tumors, is a suitable target for cancer immunotherapy. Issue 7 (3rd June 2021) - Kosaka, Akemi; Yajima, Yuki; Hatayama, Mayumi; Ikuta, Katsuya; Sasaki, Takaaki; Hirai, Noriko; Yasuda, Syunsuke; Nagata, Marino; Hayashi, Ryusuke; Harabuchi, Shohei; Ohara, Kenzo; Ohara, Mizuho; et al.
Abstract: Recent studies have revealed that tumor cells decrease their immunogenicity by epigenetically repressing the expression of highly immunogenic antigens to survive in immunocompetent hosts. We hypothesized that these epigenetically hidden "stealth" antigens should be favorable targets for cancer immunotherapy due to their high immunogenicity. To identify these stealth antigens, we treated human lung cell line A549 with DNA methyltransferase inhibitor 5‐aza‐2′‐deoxycytidine (5Aza) and its prodrug guadecitabine for 3 d in vitro and screened it using cDNA microarray analysis. We found that the gene encoding sperm equatorial segment protein 1 (SPESP1) was re‐expressed in cell lines including solid tumors and leukemias treated with 5Aza, although SPESP1 was not detected in untreated tumor cell lines. Using normal human tissue cDNA panels, we demonstrated that SPESP1 was not detected in normal human tissue except for testis and placenta. Moreover, we found using immunohistochemistry SPESP1 re‐expression in xenografts in BALB/c‐nu/nu mice that received 5Aza treatment. To assess the antigenicity of SPESP1, we stimulated human CD4 + T‐cells with a SPESP1‐derived peptide designed using a computer algorithm. After repetitive stimulation, SPESP1‐specific helper T‐cells were obtained; these cells produced interferon‐γ against HLA‐matched tumor cell lines treated with 5Aza. We also detected SPESP1 expression in freshly collected tumor cells derived from patients with acute myeloid leukemia or lung cancer. In conclusion, SPESP1 can be classified as a stealth antigen, a molecule encoded by a gene that is epigenetically silenced in tumor cells but serves as a highly immunogenic antigen suitable for cancer immunotherapy. Abstract : We identified stealth antigen SPESP1. SPESP1 is encoded by a gene silenced in tumors epigenetically, but re‐expressed in tumors exposed to a DNA methyltransferase inhibitor. SPESP1 is a highly immunogenic because a SPESP1‐derived peptide efficiently activated CD4 + T‐cells. This suggests that SPESP1 is a favorable target for cancer immunotherapy.